Europan 10 competition - Locsmándi, Gábor; Szabó, Árpád (4D Journal of Landscape Architecture and Garden Art, 2010)
The objective of Európán is to bring Europe’s young architecture and úrban design professionals to the főre, to publicize and develop their ideas. It is also the goal of the organization to help cities and developers that have provided sites to find innovative architectural and úrban Solutions for the transformation of urban locations. Európán 10 is a European federation of national organizations, which manages architectural competitions followed by building or study projects. It is launched simultaneously by several countries on common themes, objectives, and rules. The French Government founded the Pan (Programme d’Architecture Nouvelle) competition system in 1971, with the main goal of obtaining high-quality urban design and architectural projects, mainly in the field of social housing design. Parallel with the European integration processes, the French initiation was raised to a European level in 1988. In the Europan 10 competition g countries participated, while the number of participants has reached 18 countries in Europan 4.
Keywords: Europan competition; International collaboration; Rehabilitation projects